Pelatihan Hypno Public Speaking untuk Penguatan Kapasitas Komunikasi Kader Ikatan Pelajar Muhammadiyah di Era Society 5.0 - Fais Wahidatul Arifatin; Teguh Hadi Wibowo; Naajihah Mafruudloh (Universitas Muhammadiyah Manado, 2026)
The Society 5.0 era demands that the younger generation possess adaptive, persuasive, and self-confidence-based communication skills. Muhammadiyah Student Association (IPM) cadres, as agents of change within the student community, still face challenges such as public speaking anxiety, low self-confidence, and limited mastery of effective public communication techniques. This community service activity aims to improve the communication capacity of IPM cadres through hypno public speaking training, an innovative approach that combines communication techniques and psychological strengthening. The activity implementation method uses a participatory training approach with stages of needs analysis, preparation, training implementation, mentoring, and evaluation. The target group is 67 IPM cadres at the branch level. The results of the activity show a significant increase in self-confidence, message delivery structure, audience mastery, and courage to appear in public based on the results of the pre-test and post-test as well as direct observation. Participants also showed a more positive attitude change towards public communication activities. Thus, hypno public speaking training has proven effective as a strategy to strengthen the communication capacity of IPM cadres in facing the challenges of student leadership in the Society 5.0 era.